2014
DOI: 10.1108/md-08-2013-0422
|View full text |Cite
|
Sign up to set email alerts
|

The moderated relationship between job burnout and organizational cynicism

Abstract: Purpose – The purpose of this paper is to examine the relationship between two components of job burnout (emotional exhaustion and depersonalization) and organizational cynicism. Another aim of this research was to examine the role of moderating variables such as role conflict, work-family conflict, perceived fairness, and trust in coworkers on the relationship between burnout and organizational cynicism. Design/methodology/approach – Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
55
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 102 publications
9
55
0
1
Order By: Relevance
“…To some extent, these two findings supported the conclusion derived from Simha, et al;. Further, there is a significant difference in levels of exhaustion between employees of Financial Services organizations and other organization types.…”
Section: Discussion and Recommendationssupporting
confidence: 79%
“…To some extent, these two findings supported the conclusion derived from Simha, et al;. Further, there is a significant difference in levels of exhaustion between employees of Financial Services organizations and other organization types.…”
Section: Discussion and Recommendationssupporting
confidence: 79%
“…Nurses can experience detachment and a lack of compassion, ineffective communication, and loss of empathy for others (Brennan, 2017). Simha et al (2014) suggested that an essential tool to use when trying to tackle nursing turnover is to identify burnout from staff before it is too late. Burnout affects turnover, and hospital administrators need to maintain adequate staff to take care of patients, so turnover is no longer an obstacle.…”
Section: Job Burnoutmentioning
confidence: 99%
“…If a nurse quits working for any of the hospitals contributing to the blacklist, that nurse will be unable to find work with any of the other hospitals. Even if such rumors are untrue, negative perceptions of an organization's fairness may increase burnout (Ronen & Mikulincer, ; Simha, Elloy, & Huang, ).…”
Section: Data Analysis Of Er Nurse Interviewsmentioning
confidence: 99%